THE EFFECT OF QUALITY OF ACADEMIC SERVICES AND INFRASTRUCTURE ON STUDENT SATISFACTION AT UHAMKA POSTGRADUATE SCHOOL - Uswah USWAH; Hery MULJONO; Musringudin MUSRINGUDIN (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This study aims to examine: 1) the direct effect of academic service quality on student satisfaction, 2) the direct influence of infrastructure on student satisfaction, and 3) the direct influence of academic service quality on infrastructure. This study uses quantitative research methods. The target population was 318 students and the sample of research was 178 respondents. Data collection techniques are interviews and questionnaires. The research data analysis technique used path analysis. Research results prove that: first, the quality of academic services has a direct positive effect on student satisfaction. The value of the coefficient of determination is 0.527, which means that 52.7% of student satisfaction can be explained by the quality of academic services. Second, infrastructure has a direct positive effect on student satisfaction. The coefficient of determination is 0.345, which means that 34.5% of student satisfaction can be explained by infrastructure. Third, the quality of academic service has a direct positive effect on Infrastructure. The coefficient of determination is 0.137, which means that 13.7% of infrastructure can be explained by the quality of academic services.